Corporate Growth vs. Environmental Responsibility: The Path to Sustainability - syal, jyoti; Kaur, Jaspreet (RSYN Proceedings, 2025)
The environment is facing severe degradation due to rapid industrialization, pollution and modern materialistic viewpoints. Climate change, biodiversity loss, and ecosystem collapse are among the most pressing issues, driven by deforestation and unsustainable resource consumption. While the growing industry in the novel initially represents progress and prosperity, its unchecked expansion results in environmental contamination, contribute to unforeseen health crises. This message resonates with contemporary environmental concerns, as modern industries continue to pollute air, water, and soil in pursuit of economic gain. Richard Powers’ novel Gain presents a critical exploration of the effect of these issues on both human lives and the natural world which are becoming increasingly evident over time, illustrating how economic growth often comes at the expense of environmental and public health. This paper examines the moral lessons conveyed in Gain and argues for a transition toward more environmental friendly processes to mitigate further ecological harm. It is an attempt to explore possible solutions, including reaching out to stakeholders, implementing stricter environmental regulations, and investing in green technologies. By integrating these ethical considerations into real-world environmental policies, it urges a shift in the human perspective, advocating for a more harmonious relationship with nature to promote society to move towards a more sustainable future to preserve the resources of nature for the coming generations